DESAIN ISI VIDEO PEMBELAJARAN PJOK DI SD NEGERI 1 LANDASAN ULIN UTARA KOTA BANJARBARU PADA MASA PANDEMI COVID-19 DITINJAU DARI KEGIATAN GURU DALAM VIDEO - Anggraini, Yulia (MULTILATERAL PJKR JPOK, 2024)
This study aims to describe the appropriate design for the preliminary, core, and closing activities when teaching in a video subject of physical education, sports and health, located in the city of Banjarbaru. The instructional videos used in online learning and published on the KKG youtube channel in Banjarbaru City should be made based on the learning design. The samples or subjects studied in this study were public elementary schools in partnership with the gastric mangkurat university in the city of Banjarbaru, namely SD Negeri 1 Landasan Ulin Utara. Collecting data in this study from observation sheets on learning videos published on the KKG youtube channel of Banjarbaru City. The results of the research in the instructional videos for episode 1, episode 2, and episode 3, on the preliminary learning indicator with a score of 24 are classified as a moderate category. . In the learning videos for episode 1, episode 2, and episode 3 on the core indicators of learning with a score of 57, they are classified as a medium category. In the instructional videos for episode 1, episode 2, and episode 3, the learning closing indicator with a score of 18 is categorized as not good